Ultrafine eutectic Ti-Fe-based alloys processed by additive manufacturing – A new candidate for high temperature applications. (September 2020) - Gussone, Joachim; Bugelnig, Katrin; Barriobero-Vila, Pere; da Silva, Julio Cesar; Hecht, Ulrike; Dresbach, Christian; Sket, Federico; Cloetens, Peter; Stark, Andreas; Schell, Norbert; Haubrich, Jan; Requena, Guillermo
Highlights: First ultrafine Ti-Fe alloy produced by high temperature laser powder bed fusion. Characterization by synchrotron ptychographic tomography with 39 nm resolution. 3D quantification of thickness and mass density of ultrafine eutectic structures. Compression at 600 °C demonstrates high yield strength and compressive ductility. In-situ XRD during compression reveals high load bearing capability of Ti4 Fe2 Ox . Abstract: The development of metals tailored to the metallurgical conditions of laser-based additive manufacturing is crucial to advance the maturity of these materials for their use in structural applications. While efforts in this regard are being carried out around the globe, the use of high strength eutectic alloys have, so far, received minor attention, although previous works showed that rapid solidification techniques can result in ultrafine microstructures with excellent mechanical performance, albeit for small sample sizes. In the present work, a eutectic Ti-32.5Fe alloy has been produced by laser powder bed fusion aiming at exploiting rapid solidification and the capability to produce bulk ultrafine microstructures provided by this processing technique. Process energy densities between 160 J/mm³ and 180 J/mm³ resulted in a dense and crack-free material with an oxygen content of 0.45 wt.% in which a hierarchical microstructure is formed by µm-sized η-Ti4 Fe2 Ox dendrites embedded in an ultrafine eutectic β-Ti/TiFe matrix. The microstructure was studied three-dimensionally using near-field synchrotron ptychographic X-ray computed tomography with an actual spatial resolution down to 39 nm to analyse the morphology of the eutectic and dendritic structures as well as to quantify their mass density, size and distribution. Inter-lamellar spacings down to 30–50 nm were achieved, revealing the potential of laser-based additive manufacturing to generate microstructures smaller than those obtained by classical rapid solidification techniques for bulk materials. The alloy was deformed at 600 °C under compressive loading up to a strain of 30% without damage formation, resulting in a compressive yield stress of 800 MPa. This study provides a first demonstration of the feasibility to produce eutectic Ti-Fe alloys with ultrafine microstructures by laser powder bed fusion that are suitable for structural applications at elevated temperature. Graphical abstract: Image, graphical abstract